Cervical Spondylodiscitis in an Infant with Torticollis. Issue 1 (10th June 2021) - Van Berkel, Brecht; Suetens, Kristin; Breysem, Luc
Teaching point: Narrowing of the intervertebral space and destruction of the adjacent vertebral end plates on conventional radiography or CT should raise suspicion for spondylodiscitis in symptomatic infants.